SKILLS, ATTITUDE AND CHALLEGES TOWARDS THE APPLICATION OF LMS LEARNING MANAGEMENT SYSTEM AT THE JIANGXI PROVINCE IN CHINA: A CASE STUDY - Hu Qinglin; Noraini Hj Zainal Abidin (Journal of Islamic, Social, Economics and Development, 2024)
In recent years, the adoption of Learning Management Systems (LMS) has been a pivotal development in the field of education, offering a digital platform that facilitates teaching and learning. This case study specifically focuses on Jiangxi Province in China, aiming to understand the dynamics of LMS implementation within this region. Jiangxi Province, with its diverse educational landscape, presents a unique context for investigating the skills, attitudes, and challenges surrounding the application of LMS. The study investigates the skills required for educators and students to effectively harness the potential of LMS, considering technological proficiency, content development, and interactive engagement. It also explores the evolving attitudes of both educators and students towards digital learning platforms, shedding light on the adaptation process and the changing paradigms in education. Furthermore, this research delves into the challenges faced in the implementation of LMS in Jiangxi Province. These challenges may encompass issues such as infrastructure limitations, pedagogical adjustments, and the digital divide. Understanding these challenges is critical to devising effective strategies for the successful integration of LMS in the province's educational system. By shedding light on the skills, attitudes, and challenges, this study provides valuable insights for educators, policymakers, and stakeholders in Jiangxi Province and offers a broader perspective on LMS adoption in the global educational context.